Awareness Regarding Causes of Infertility among Out-patients at a Tertiary Care Hospital in Lahore, Pakistan - Zobia Jawad, Rubina Mustafa, Anikah Kanwal, Sadia Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To assess the general awareness regarding infertility and its causes; and identify, key knowledge gaps if any, related to the subject. Study Design: A cross-sectional study. Period: January, 2019 to December 2019. Setting: Lady Willingdon Hospital, Lahore, Pakistan. Material and Methods: Data collection was done by convenient sampling technique, from the 500 female participants (18 years and above) through an interview-based questionnaire (Cardiff Fertility Knowledge Scale, CFKS) , there was an assessment of the knowledge related to the causes leading to infertility such as lifestyle, smoking, use of contraception, infections of genital tract etc. There was determination of the association between socio-demographic variables and their mean knowledge scores. Data were analyzed using SPSS version 20. Results: The majority of the participant population (67%, n=340) was married, about more than half of the population was unemployed (n=280) compared to the employed population (n=220). While, nearly half of the participants (n=248, 49.5 %) did not believe that males and females contribute to infertility equally. The mean knowledge score of the study participants was 12.95 ± 2.48 points. The participants (n=165, 32%) believed that the previous usage of the intra-uterine device leads to infertility. Moreover, more than half of the participants (n=278, 55.9%) wrongly believed that a male partner achieving erection is a sign of fertility. Education (p=0.019) and marital status (p=0.03) were the only demographic factors that showed major differences with mean knowledge scores. Conclusion: It was found out that the awareness in the general population about the infertility and its causes was lacking. It is important that the education regarding the fertility related issues be more common, that can be planned through various awareness programs, workshops and seminars. This in turn can help the couples by directing them to seek timely and more focused medical help. Keywords: Infertility, knowledge, awareness, developing country.